Identification of Pathogenic Cardiac CD11c+ Macrophages in Nod1-Mediated Acute Coronary Arteritis. Issue 6 (June 2015) - Motomura, Yoshitomo; Kanno, Shunsuke; Asano, Kenichi; Tanaka, Masato; Hasegawa, Yutaka; Katagiri, Hideki; Saito, Takashi; Hara, Hiromitsu; Nishio, Hisanori; Hara, Toshiro; Yamasaki, Sho
<x xml:space="preserve">Abstract</x> Objective— Nod1 is an intracellular pattern recognition receptor for bacterial peptidoglycan fragments. We previously reported that a synthetic Nod1 ligand, FK565, induced acute coronary arteritis in mice similar to that of Kawasaki disease. However, the molecular mechanisms underlying this characteristic inflammation have remained elusive. Approach and Results— We found that CD11c+MHC class II+ cells accumulated in the heart of FK565-treated mice before arteritis development. Morphological features and gene expression signatures of the cardiac CD11c+MHC class II+ cells suggested that this population is closely related to macrophages, and thus, we designated them cardiac CD11c+ macrophages. Nod1 in nonhematopoietic cells, rather than hematopoietic cells, was required for the increase of cardiac CD11c+ macrophages and arteritis development. Among nonhematopoietic cells, cardiac endothelial cells produced a large amount of chemokines in response to FK565. Endothelial cell–specific blockade of Nod1 signaling suppressed FK565-induced expression of these chemokines, accumulation of cardiac CD11c+ macrophages, and subsequent coronary arteritis development. We also found that CCR2+Ly6Chi inflammatory monocytes in peripheral blood supplied precursors of cardiac CD11c+ macrophages. CCR2-deficient mice or pertussis toxin–treated mice exhibited decreased numbers of cardiac CD11c+ macrophages and reduced arteritis. Conclusions— These results suggest that Ly6Chi monocytes are recruited to FK565-activated endothelial cells to generate cardiac CD11c+ macrophages, which play a pivotal role in the pathogenesis of acute coronary arteritis.